A Case of Hydralazine-Induced ANCA Vasculitis/Lupus Overlap Syndrome Presenting as Persistent Bicytopenia - Madiha Naqsh Siddiqui; Stephanie Norris (Case Reports in Rheumatology)
Conclusions: This case report helps highlight the vague symptoms that can be associated with hydralazine-induced vasculitis/lupus overlap syndrome. This case will increase clinician awareness for early recognition of such a syndrome, prompting early diagnosis, preventing end-organ damage, reducing hospitalizations and improving quality of life.